Study on Compound Percussive Drilling: Rock‐Breaking Mechanism of High Confining Pressure Formation in the East China Sea - Jiwei Li (Energy Science & Engineering, 2025)
ABSTRACT The effect of improving the depth of penetration (ROP) in deep, high‐confining pressure formation is closely related to the rock‐breaking method, which has become a bottleneck restricting the efficient development of oil and gas. Based on the current engineering practice of the Xihu block in the East China Sea Basin, experimental research on rock mechanical characteristics in deep strata was carried out, and a three‐dimensional rock‐breaking numerical model of the compound percussive system was established to simulate the dynamic single‐cutter‐rock interaction. The sensitivity analysis investigated the effects of the dynamic load impact frequency, axial and circumferential stress load, and static and dynamic loading time ratio on the penetration depth of drilling teeth in compound percussive drilling. As revealed from the results, the attenuation coefficients of stress waves in the medium are different under different frequencies. The higher the frequency of stress wave attenuation, the faster the fluctuation range of penetration depth decreases, and the rock‐breaking effect decreases. With the continuous increase of dynamic load, the damage below the cutting plane first increases and then decreases. The size of cuttings decreases first and then increases as the ratio of static and dynamic loads increases. With the increase of the ratio of axial and circumferential static and dynamic loading time, the fluctuation range of penetration depth decreases, and the overall penetration fluctuation decreases. Finally, the field applications of compound percussive drilling were conducted. Matching higher impact frequency under low‐speed conditions and lower impact frequency under higher‐speed conditions is recommended, which is conducive to maximizing the impact drilling tool's role. The research results can provide a theoretical basis for exploring deep‐formation rock‐breaking mechanisms and optimizing the engineering parameters of percussion drilling tools.